Accuracy Analysis of a Next-Generation Tissue Microarray on Various Soft Tissue Samples of Wistar Rats - Werry, Jan-Erik; Müller, Stefan; Wehrhan, Falk; Geppert, Carol-Immanuel; Frohwitter, Gesche; Kaemmerer, Peer W.; Möst, Tobias; Lutz, Rainer; Homm, Andi; Kesting, Marco Rainer; Weber, Manuel; Ries, Jutta (Applied Sciences, 2021)
This study aimed to investigate accuracy in different sectional planes of the TMA Grand Master (3DHISTECH) Workstation in various soft tissue samples collected from Wistar rats. A total of 108 animals were sacrificed and 963 tissue specimens collected from 12 soft-tissue types. A total of 3307 tissue cores were punched and transferred into 40 recipient TMA blocks. Digital image analysis was performed. Core loss showed a significant correlation with tissue type and was highest in skin tissue (p < 0.001), renal medulla and femoral artery, nerve, and vein bundle (p < 0.01). Overall, 231 of 3307 tissue cores (7.0%) were lost. Hit rate analysis was performed in 1852 punches. The target was hit completely, partially and missed totally by 89.4%, 7.2% and 2.2%. A total of 54.5% of punches had good accuracy with less than 200 mu m deviation from the centre of the targeted region and 92.6% less than 500 mu m. Accuracy decreases with greater sectional depth. In the deepest sectional plane of roughly 0.5 mm median depth, almost 90% of cores had a deviation below 500 mu m. Recommendations for automated TMA creation are given in this article. The ngTMA(R)-method has proven accurate and reliable in different soft tissues, even in deeper sectional layers.
CRIS-Team WoS Importer:2021-07-09